ANALISIS PENGENDALIAN KUALITAS UNTUK MENGURANGI DEFECT PADA GLASS BOTTLE DENGAN MENGGUNAKAN METODE QUALITY CONTROL CIRCLE PT MULIAGLASS CONTAINER DIVISION CIKARANG JAWA BARAT - Dadang Surya Kencana; Elis Chalisyah; Yollanda Riswana Azhari (POLITEKNIK LP3I JAKARTA, 2024)
PT Muliaglass Container Division is a subsidiary of PT Mulia Industrindo, Tbk which is engaged in the glass industry by producing flat glass, glass block, glass packaging, and automotive safety glass as a result of its production. PT Muliaglass Container Division was founded in 1989. The quality control carried out by PT Muliaglass Container Division experienced problems in the Quality Control section or checking checkers, resulting in the defect pass rate so far exceeding the tolerance limits set by the company. There are several types of product defects in glass bottle packaging at PT Muliaglass Container Division, namely Check Ring, Check Under Ring, Leaner, Hot Mold Check, and others. To overcome the problems encountered, research is needed using the Quality Control Circle Method and Statistical Quality Control which are used to calculate how big the reasonable limit is in the product pass rate. After processing Statistical Quality Control data and knowing the number of acceptable quality labels for passing controlled defects or not, proceed with the Quality Control Circle Method, to find out what causes product defects to pass.